زيادة المناعة الضجيجية في نظام التلفزة - عيسى سمير (Latakia University Journal -Engineering Sciences Series, 2019)
تُستخدم في قناة التكبير في نظام التلفزة عدة إجراءات لتخفيض مستوى الضجيج المرافق للإشارة التلفزيونية وتخفيض ملحوظيته على شاشة أنبوب الصورة التلفزيوني. ويتم خفض مستوى الضجيج العشوائي باستخدام مخمِّدات الضجيج ودارات التصحيح. تتحدد أهمية هذه الإجراءات بالحرص على زيادة حساسية نظام التلفزة، مع الأخذ بعين الاعتبار أن تصحيح أي نوع من التشوهات التي تتعرض لها الإشارة يترافق بزيادة مستوى الضجيج. يعرض هذا البحث طريقة الترشيح الخطي لزيادة نسبة الإشارة إلى الضجيج دون أن يؤثر ذلك على استبانه الصورة التلفزيونية. Quite a number of measures are taken in the amplifier section of TV system to minimize the noise content of the TV signal and the visibility of spurious components in the picture. Notably, the level of fluctuation noise is brought down through a proper design of input circuits, noise cancellation, and noise suppression. These measures are important as they enhance the sensitivity of the system, but one ought not neglect the fact that the compensation of any impairment in the TV signal is, as a rule, accompanied by a rise in the noise level. This paper presents a simple method to increase the signal-noise ratio by linear filtration with out any impact on the picture resolution.